Assessment of the effects of acetic, oxalic, and tricarballylic acids on struvite crystallization: characterisation and kinetic studies - SAYAN, PERVİZ; POLAT, SEVGİ (TAYLOR & FRANCIS LTD, 2021)
This work reports the characteristics and thermal decomposition kinetics of struvite crystals prepared with and without acetic acid, oxalic acid, and tricarballylic acid as additives. Firstly, the structure, functional groups, surface charge, morphology, particle size, and filtration characteristics of the crystals prepared with and without the additives were determined. All carboxylic acids used in this study were found to significantly affect the surface electrical charge, size, and morphology of the prepared struvite crystals. FTIR analysis revealed the presence of various functional groups in the struvite. With oxalic acid as the additive at a concentration of 200 ppm, the struvite was the most filterable with the lowest cake resistance and highest filtration rate. In the next step, the thermal decomposition of the crystals was examined and the obtained data were used to investigate the dehydration kinetics of the struvite based on a Coats-Redfern kinetic model. The average activation energies of struvite crystals prepared without and with acetic, oxalic, and tricarballylic acid were calculated to be 134.5, 96.3, 111.5, and 97.0 kJ/mol, respectively. Thus, the results of this work are useful for selection of a struvite morphology modifier and explaining the mechanism of the dehydration kinetics of struvite crystals.
Keywords: Struvite; morphology; crystallization; carboxylic acid; kinetics; PHOSPHORUS RECOVERY; CITRIC-ACID; PRECIPITATION; CALCIUM; MINERALIZATION; PARAMETERS; CRYSTALS; REMOVAL